Matkailurakentaminen ja sen diskursiivinen rakentuminen Kilpisjärvellä - Mäkitie, Tuukka (Helsingfors universitet, 2010)
This master s thesis examines tourism related housing and related discourses in the village of Kilpisjärvi, Finland. I study the tourism development in Kilpisjärvi and the debate related to this process. My methodology is based on discourse and content analysis. The purpose of this study is to examine and classify the discourses of tourism related housing and what are the lessons learned from the recent development of Kilpisjärvi. Kilpisjärvi is the northernmost village in western Finnish Lapland, located in the middle of the highest mountain area of Finland. The area has been reindeer herding area of Saami people for centuries, but it has lacked permanent settlement until the beginning of 20th century. The first tourist accommodation was built in 1930s, followed by the road in 1940s and the hotel in 1950s. Traditionally the area has attracted skiers and hikers. The area is also known for its extraordinary nature and rare plant life. Tourism development was slow in Kilpisjärvi until the turn of millennium when rapid growth in tourism related housing was triggered by extensive land use planning. Small wilderness village of Kilpisjärvi has grown to a tourism centre with over 800 beds in commercial enterprises, more than hundred second-homes, and two large caravan areas. This development has raised conflicts among villagers. The empirical part of this study is based on the interviews of 17 permanent dwellers of Kilpisjärvi and three Norwegian cottage owners. Six discourses can be distinguished: 1) Nature and landscape, 2) Economy, 3) Place, 4)Reindeer herding, 5) Governance and 6) Possibilities to influence decision-making. The first discourse stressed that tourism development and building should adapt to nature and landscape, while economic discourse stressed the economical importance of tourism to Kilpisjärvi and the municipality of Enontekiö. The third discourse noted the change of Kilpisjärvi as a place due to the boom of tourism development. The discourse of reindeer herding was clearly distinguished from ...